Управление финансовой устойчивостью предприятий - Верна, В.В. (Культура народов Причерноморья, 2014)
Рассмотрено значение финансовой устойчивости в деятельности предприятий, описаны
основные подходы к определению финансовой устойчивости, а также базовые стратегии и субстратегии
поддержания финансовой устойчивости предприятия. Выявлены внешние и внутренние факторы, влияющие
на финансовую устойчивость предприятия, а также средства оперативной нейтрализации риска снижения
финансовой устойчивости. Розглянуто значення фінансової стійкості в діяльності підприємств, описані основні підходи до
визначення фінансової стійкості, а також базові стратегії і субстратегії підтримання фінансової
стійкості підприємства. Виявлені зовнішні та внутрішні фактори, що впливають на фінансову стійкість
підприємства, а також засоби оперативної нейтралізації ризику зниження фінансової стійкості. Further developed theoretical concepts, methodological approaches and to develop recommendations for
the formation of a strategic framework of financial stability of modern enterprises. In this paper the importance and
urgency of the issues management and strategic planning for the financial sustainability of the crisis at the present
stage of development of the economy. Discusses the importance of financial stability in the activity of enterprise , the
basic approaches to the problem of quantifying the financial stability and the basic strategies that must comply with the
instructions for maintaining the financial stability of the company. Identification of external and internal factors
affecting the financial stability of the enterprise , as well as a means to reduce operational risk neutralization of
financial stability. Sub-strategies have been developed to govern the financial stability of enterprises.